Synthesis, Structural Characterization And Anticancer Studies Of Asymmetrical And Symmetrical Dinuclear Silver(I) Di-nheterocyclic Carbene Complexes - Nazri, Muhammad Zulhelmi (2022)
This thesis presents the synthesis, structural characterization, and anticancer studies of asymmetrical and symmetrical dinuclear silver(I) di-N-heterocyclic carbene (NHC) complexes which are mainly derived from bis- and tetrakis-benzimidazolium salts. The asymmetrical bis-benzimidazolium salts were prepared in two different substituents series comprising N-(2-bromoethyl)-N’-benzylbenzimidazolium bromide with R-alkyl group (R = CH3, C2H5, C3H7, C4H9, C5H11 and C6H13) (1‧Br – 6‧Br) as the first series and R-aryl group (R = 2-CN, 3-CN and 4-CN) (7‧Br – 15‧PF6) as the second series consisting of ethylene, propylene and butylene bridges, respectively. As for the symmetrical tetrakis-imidazolium salt was comprised reaction of 1,2,4,5- tetrakis(bromomethyl)benzene with imidazole moiety of 16‧Br. All the asymmetry bis-benzimidazolium and symmetry tetrakis-imidazolium salts were converted into their respective complexes by in-situ deprotonation reaction with Ag2O by varying the salt and metal molar ratio, thus resulting the formation of dinuclear silver(I) di-NHC complexes (Ag1 – Ag16). The structures of the bis-benzimidazolium (1‧Br – 15‧PF6), tetrakis-imidazolium (16‧Br) salts as well as Ag(I) di-NHC complexes (Ag1 – Ag16) were characterized by combination of spectroscopic data (FTIR, 1H- and 13C-NMR), CHN elemental analysis and single crystal X-ray diffraction technique. The single crystal X-ray diffraction studies of complex Ag4 suggest the complex crystallized in orthorhombic space group while the macrocyclic complex of Ag16 has cylinder-type structure.